The Influence of Hemodialysis Adequacy on the Blood Urea Value - Retno Agustiyowati, Tri Hapsari (KnE Life Sciences, 2019)
Hemodialysis is one of the substitutional renal therapies given to chronic renal clients who are experiencing terminal stage or end-stage Renal Diseases (ESRD). In Indonesia, there are 655 renal units and 433 among them have sent the data to Indonesia Renal Registry (IRR). There are 77,892 clients who do hemodialysis therapy actively. Therefore, among them, 30,831 are new clients who have just started taking the therapy. Hemodialysis is a therapy to get rid of the toxic, water and soluble essence from the blood in clients who have ESRD. The success of hemodialysis can be known from the HD adequacy. The research aims to identify the influence of hemodialysis adequacy on the blood urea value and the research was conducted at the TK.II Dustira Cimahi Hospital. The research used quantitative with different tests. Ninety respondents were involved in the research by using a convenience sampling technique. Adequacy HD was calculated by using a calculator online KT/V and blood urea was obtained from the medical record of secondary data from the laboratory checking the pre and post HD urea blood. Analysis data used paired t-test. The research result showed that HD adequacy average was 1,27 and the urea average of pre HD was 165 mg/dl, furthermore the average of post urea HD was 59,93 mg/dl. The result of the analysis with paired t-test showed that there is an influence of hemodialysis adequacy on the blood urea value with p-value = 0,00 (p<0,05). Therefore, it can be concluded that there is an influence of hemodialysis adequacy towards the blood urea value. The suggestion for the renal unit is to increase the HD adequacy that aims to reduce blood urea value.